2002
DOI: 10.1023/a:1020600520233
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Intravenous injection of chloramine derivatives of amino acids and taurine reduced the mortality rate in mice with thrombosis induced by intravenous injection of ADP or collagen-epinephrine mixture. Intravenous injection of N,N-dichlorotaurine caused 50% inhibition of platelet aggregation induced by ADP and measured in the platelet-enriched plasma in vitro. The antithrombotic effect of chloramine derivatives of amino acids and taurine is related to their ability to suppress functional activity of platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…The chloramine derivatives of amino acids react with sulfur-containing groups and modify platelet membrane, which results in generalized inhibition of functional activity of platelets (inhibition of its activation irrespective of agonist nature) [1][2][3][4]10]. Inhibition of aggregation of the platelets depends on their structure and physicochemical parameters of N-chloramine acids such as their molecular weight and van der Waals volume.…”
mentioning
confidence: 99%
“…The chloramine derivatives of amino acids react with sulfur-containing groups and modify platelet membrane, which results in generalized inhibition of functional activity of platelets (inhibition of its activation irrespective of agonist nature) [1][2][3][4]10]. Inhibition of aggregation of the platelets depends on their structure and physicochemical parameters of N-chloramine acids such as their molecular weight and van der Waals volume.…”
mentioning
confidence: 99%
“…ADP-induced PA in PRP is inhibited by a number of chloramine derivatives of amino acids, the antiaggregant effect of these compounds depends on their structure [2,6]. First, comparison of antiaggregant activity of biochloramines with different location of chloramine group in the molecule showed that the compounds where the chloramine group is located at a distance of 3-5 carbon atoms from the carboxyl group are most effective.…”
Section: Resultsmentioning
confidence: 99%
“…First, comparison of antiaggregant activity of biochloramines with different location of chloramine group in the molecule showed that the compounds where the chloramine group is located at a distance of 3-5 carbon atoms from the carboxyl group are most effective. The existence of a negatively charged group at the site of biochloramine interaction with the plasma membrane responsible for this structural feature was hypothesized [6]. Second, it was found that antiaggregant effect of chloramine derivatives of amino acids on platelets in PRP after addition of ADP depends on their molecular weight (size of molecule) [2] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations